Svenska generiska pronomen hos finska språkbadselever. En jämförelse mellan två årskurser - Nyqvist, Eeva-Liisa; Lindström Tiedemann, Therese (Folia Scandinavica Posnaniensia, 2023)
This is a study of the use of generic pronouns in Swedish as a second language (L2) by L1 Finnish immersion students. We compare two groups, 12-year-olds, and 15-year-olds, to see if there is a difference and to identify which the most challenging cases are in both groups. Norm deviations are compared to see if they mainly consist of overuse of generic pronouns or more formal aspects, such as the pronoun which is chosen, and the understanding of the relation between the generic subject, object, possessive and reflexive pronouns. Both groups use generic pronouns in the subject position in a manner which mostly follows the standard, and mainly have problems with possessive pronouns in connection to generic pronouns. It is possible that object generic pronouns would also be problematic, but there are none in our data. Generic pronouns are sometimes left out as subjects, which is ungrammatical in Swedish. There is also occasional overuse of man where it is not idiomatic, and some mixed forms with man and s-passive. Results show possible transfer from the first language (L1) of the learners, but less in the older group. Furthermore, there also appears to be transfer from L3 English, which our informants are learning at school. This seems more present in the older group.